A Phase‐Changing Polymer Film for Broadband Smart Window Applications. Issue 16 (21st July 2020) - Xie, Yu; Guan, Fangyi; Li, Zhou; Meng, Yuan; Cheng, Jiang; Li, Lu; Pei, Qibing
Abstract: Smart windows (SWs) with tunable opacity are sought to regulate solar‐irradiation and privacy protection. A new smart window material based on a phase‐changing polymer that can be reversibly switched between a semicrystalline, opaque state and an amorphous, transparent state is introduced. The polymer film is a network of the phase‐changing poly(stearyl acrylate) crosslinked with a poly(ethylene oxide) oligomer. The two constituent polymers show strong phase separation. The transmission switching of the resulting copolymer film is resulted from the combination of three different mechanisms: reversible phase changing of the poly(stearyl acrylate) component, phase separation between the two distinct constituent polymers, and a large change of refractive index of the phase‐changing polymer during the amorphous‐to‐semicrystalline transition. The opaqueness switching can be reversed and repeated for more than 500 cycles of heating and cooling. A silver nanowire (AgNW)‐based transparent heater is combined with the SW film to control the semicrystalline‐to‐amorphous phase transition. The resulting smart window exhibits a high infrared transmittance modulation (Δ T IR ) of 80.4% and solar transmittance modulation (Δ T solar ) of 70.2%, which significantly outperform existing thermochromic smart windows. Abstract : A new smart window material is introduced for wide‐bandwidth optical modulation. Its opacity is switched based on differential change of refractive indices in a phase separated copolymer. The solid‐state copolymer film is opaque at ambient temperature and turns transparent above 46 °C, with solar transmittance modulation of 70% and infrared transmittance modulation of 80%.